1999
DOI: 10.1063/1.124713
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-based single-electron memory using a multiple-tunnel junction fabricated by electron-beam direct writing

Abstract: Multiple-tunnel-junction-based nonvolatile single-electron-memory devices are promising for fast write/erase operation and long retention time. Fabrication of multiple-tunnel junctions with a predetermined number of barriers and islands is a major problem in realizing such devices. We have fabricated multiple-tunnel-junction-based single-electron devices by an electron-beam direct writing technique in a silicon-on-insulator layer. Using this technique, it is possible to fabricate multiple ultrasmall islands an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In 1993, Yano et al demonstrated controlled room-temperature storage of individual electrons in such nanoscale floating gates. 1 Multiple tunnel junction (MTJ) memories [2][3][4][5] are expected to have considerably faster write speeds than flash memories due to a reduced tunnel junction resistance. The memory function in MTJ memories is attained by trapping of electrons in metastable states.…”
mentioning
confidence: 99%
“…In 1993, Yano et al demonstrated controlled room-temperature storage of individual electrons in such nanoscale floating gates. 1 Multiple tunnel junction (MTJ) memories [2][3][4][5] are expected to have considerably faster write speeds than flash memories due to a reduced tunnel junction resistance. The memory function in MTJ memories is attained by trapping of electrons in metastable states.…”
mentioning
confidence: 99%
“…Details of the electrical characteristics of these devices have been reported separately. 13 The retention time of electrons in the storage island, estimated from the gate voltage sweeping speed, is at least 4 h at 20 K.…”
Section: B Electrical Characteristicsmentioning
confidence: 99%
“…Extraordinary ingenuity has been applied to demonstrate basic single-electron logic circuits in silicon [2,3], but the problem of random polarization o sets on each Coulomb island continues to block e orts toward higher levels of integration. While single-charge phenomena may ÿnd important memory applications within present technology [4][5][6], advanced computation is di cult to imagine in the presence of random o sets.…”
Section: Introductionmentioning
confidence: 99%